SEAMLESS PAYMENT PROCESSING: LEVERAGING REAL-TIME RISK ASSESSMENT FOR ECOMMERCE - Arpit Mathur , (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This comprehensive article explores the evolution and implementation of real-time risk assessment systems in eCommerce payment processing. The article examines the limitations of traditional fraud detection approaches and presents modern solutions that combine advanced technologies, machine learning, and sophisticated data analysis frameworks. It investigates the benefits for both platforms and customers, including enhanced fraud detection, improved customer experience, and increased operational efficiency. The article also outlines critical success factors, implementation guidelines, and emerging trends in digital payment security, providing a roadmap for organizations seeking to implement or upgrade their risk assessment capabilities while maintaining regulatory compliance and optimal user experience.